Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Absolutely, I can assist with that!
To find [tex]\( f(c) \)[/tex] using synthetic substitution, we'll apply the process to the polynomial [tex]\( f(x) = -x^7 + 4x^6 - 4x^5 - 6x^4 - 3x^3 - 6x^2 - x - 2 \)[/tex] for [tex]\( c = -5 \)[/tex].
Here is the step-by-step synthetic substitution process:
1. Write down the coefficients of the polynomial:
- Coefficients: [tex]\([-1, 4, -4, -6, -3, -6, -1, -2]\)[/tex]
2. Set up the synthetic substitution:
- We have [tex]\( c = -5 \)[/tex].
- Place the coefficients in the synthetic substitution setup.
3. Perform the synthetic substitution:
- Start with the leading coefficient:
[tex]\[ -1 \][/tex]
- Multiply by [tex]\( c \)[/tex] and add the next coefficient:
[tex]\[ -1 \cdot (-5) + 4 = 9 \][/tex]
- Continue this process through all coefficients:
Here is the step-by-step computation:
[tex]\[ \begin{array}{c|rrrrrrrr} -5 & -1 & 4 & -4 & -6 & -3 & -6 & -1 & -2 \\ \hline & -1 & 9 & -49 & 239 & -1198 & 5984 & -29921 & 149603 \\ \end{array} \][/tex]
Breaking it down:
- First step:
[tex]\( -1 \cdot (-5) + 4 \Rightarrow 5 + 4 = 9 \)[/tex]
[tex]\(\rightarrow\)[/tex] Second coefficient becomes 9
- Second step:
[tex]\( 9 \cdot (-5) + (-4) \Rightarrow -45 - 4 = -49 \)[/tex]
[tex]\(\rightarrow\)[/tex] Third coefficient becomes -49
- Third step:
[tex]\( -49 \cdot (-5) + (-6) \Rightarrow 245 - 6 = 239 \)[/tex]
[tex]\(\rightarrow\)[/tex] Fourth coefficient becomes 239
- Fourth step:
[tex]\( 239 \cdot (-5) + (-3) \Rightarrow -1195 - 3 = -1198 \)[/tex]
[tex]\(\rightarrow\)[/tex] Fifth coefficient becomes -1198
- Fifth step:
[tex]\( -1198 \cdot (-5) + (-6) \Rightarrow 5990 - 6 = 5984 \)[/tex]
[tex]\(\rightarrow\)[/tex] Sixth coefficient becomes 5984
- Sixth step:
[tex]\( 5984 \cdot (-5) + (-1) \Rightarrow -29920 - 1 = -29921 \)[/tex]
[tex]\(\rightarrow\)[/tex] Seventh coefficient becomes -29921
- Seventh step:
[tex]\( -29921 \cdot (-5) + (-2) \Rightarrow 149605 - 2 = 149603 \)[/tex]
[tex]\(\rightarrow\)[/tex] Final outcome becomes 149603
Final numbers obtained from the synthetic substitution process are:
[tex]\[ [-1, 9, -49, 239, -1198, 5984, -29921, 149603] \][/tex]
Thus, [tex]\( f(-5) \)[/tex] evaluates to [tex]\( 149603 \)[/tex].
To find [tex]\( f(c) \)[/tex] using synthetic substitution, we'll apply the process to the polynomial [tex]\( f(x) = -x^7 + 4x^6 - 4x^5 - 6x^4 - 3x^3 - 6x^2 - x - 2 \)[/tex] for [tex]\( c = -5 \)[/tex].
Here is the step-by-step synthetic substitution process:
1. Write down the coefficients of the polynomial:
- Coefficients: [tex]\([-1, 4, -4, -6, -3, -6, -1, -2]\)[/tex]
2. Set up the synthetic substitution:
- We have [tex]\( c = -5 \)[/tex].
- Place the coefficients in the synthetic substitution setup.
3. Perform the synthetic substitution:
- Start with the leading coefficient:
[tex]\[ -1 \][/tex]
- Multiply by [tex]\( c \)[/tex] and add the next coefficient:
[tex]\[ -1 \cdot (-5) + 4 = 9 \][/tex]
- Continue this process through all coefficients:
Here is the step-by-step computation:
[tex]\[ \begin{array}{c|rrrrrrrr} -5 & -1 & 4 & -4 & -6 & -3 & -6 & -1 & -2 \\ \hline & -1 & 9 & -49 & 239 & -1198 & 5984 & -29921 & 149603 \\ \end{array} \][/tex]
Breaking it down:
- First step:
[tex]\( -1 \cdot (-5) + 4 \Rightarrow 5 + 4 = 9 \)[/tex]
[tex]\(\rightarrow\)[/tex] Second coefficient becomes 9
- Second step:
[tex]\( 9 \cdot (-5) + (-4) \Rightarrow -45 - 4 = -49 \)[/tex]
[tex]\(\rightarrow\)[/tex] Third coefficient becomes -49
- Third step:
[tex]\( -49 \cdot (-5) + (-6) \Rightarrow 245 - 6 = 239 \)[/tex]
[tex]\(\rightarrow\)[/tex] Fourth coefficient becomes 239
- Fourth step:
[tex]\( 239 \cdot (-5) + (-3) \Rightarrow -1195 - 3 = -1198 \)[/tex]
[tex]\(\rightarrow\)[/tex] Fifth coefficient becomes -1198
- Fifth step:
[tex]\( -1198 \cdot (-5) + (-6) \Rightarrow 5990 - 6 = 5984 \)[/tex]
[tex]\(\rightarrow\)[/tex] Sixth coefficient becomes 5984
- Sixth step:
[tex]\( 5984 \cdot (-5) + (-1) \Rightarrow -29920 - 1 = -29921 \)[/tex]
[tex]\(\rightarrow\)[/tex] Seventh coefficient becomes -29921
- Seventh step:
[tex]\( -29921 \cdot (-5) + (-2) \Rightarrow 149605 - 2 = 149603 \)[/tex]
[tex]\(\rightarrow\)[/tex] Final outcome becomes 149603
Final numbers obtained from the synthetic substitution process are:
[tex]\[ [-1, 9, -49, 239, -1198, 5984, -29921, 149603] \][/tex]
Thus, [tex]\( f(-5) \)[/tex] evaluates to [tex]\( 149603 \)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.